2017
DOI: 10.5861/ijrset.2017.1703
|View full text |Cite
|
Sign up to set email alerts
|

The learning effects of using infant simulators in Family Life Education: A study of undergraduate students in Taiwan

Abstract: The purpose of this study explored the perceptions of undergraduate students who employed simulator infants in Family Life Education. All of the participants (N=156) were undergraduate students majoring in Family Studies programs in Taiwan. The data collection included quantitative reports of proper care scores, questionnaire, and qualitative data from focus group interviews and students' reflective journals. The results showed that participants realized the responsibilities, challenges and difficulties of car… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
11
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(12 citation statements)
references
References 16 publications
1
11
0
Order By: Relevance
“…These findings suggest that infant simulators can be successfully embedded into an active learning-based undergraduate workshop and, according to the students, serve as an effective tool for developing their understanding and encouraging higher level thinking about developmental concepts. In adopting a research-informed approach to the workshop, based on Voorthuis et al's (2013) laboratory-based LISSA procedure, this pilot study extends previous findings based on research that has used infant simulators in undergraduate classes (e.g., Bath et al, 2000;Jang & Lin, 2017) by demonstrating that the equipment can be used to contribute to students' learning as well as shaping their attitudes and beliefs about parenting.…”
Section: Discussionsupporting
confidence: 70%
See 1 more Smart Citation
“…These findings suggest that infant simulators can be successfully embedded into an active learning-based undergraduate workshop and, according to the students, serve as an effective tool for developing their understanding and encouraging higher level thinking about developmental concepts. In adopting a research-informed approach to the workshop, based on Voorthuis et al's (2013) laboratory-based LISSA procedure, this pilot study extends previous findings based on research that has used infant simulators in undergraduate classes (e.g., Bath et al, 2000;Jang & Lin, 2017) by demonstrating that the equipment can be used to contribute to students' learning as well as shaping their attitudes and beliefs about parenting.…”
Section: Discussionsupporting
confidence: 70%
“…Bath et al (2000) reported that undergraduate medical students did not find the simulator realistic and the researchers did not deem the technology as useful in helping these students to understand parenting, knowledge that would support their practice with real-life parents. Jang and Lin (2017) reported that undergraduate students in a family studies course found interacting with the simulators made them think about parenting (e.g., responsibilities and practicalities). Researchers have also used infant simulators to examine adults' reactions to infant crying (e.g., Bruning & McMahon, 2009) and, more recently, attachment-related concepts in the form of caregiver sensitivity (e.g., Bakermans-Kranenburg, Alink, Biro, Voorthuis, & van Ijzendoorn, 2015;Voorthuis, et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Although the data showed that the students could identify each of the needs of the simulator, the proper care score was low (Md 53.5%, range 21–81) and two of the students had an abuse shutdown within the 48 hr of care. In a recent study among undergraduate students ( n = 156) aged 18–22, the mean proper care was 94.18% ( SD 6.67, range 64–100; Jang & Lin, ). The great difference in proper care in a general teenage population compared to these students with intellectual disability can possibly be explained by individual differences, but it can also be due to other factors, for example choice of the intervention‐period during weekdays.…”
Section: Discussionmentioning
confidence: 98%
“…Even after a noncompleted simulation period, the discussion around the students’ experiences from the intervention is crucial. Also, in the Japanese study (Jang & Lin, ), the participants received an instruction handbook to have at home. As this was not done in the present study, one reason for the low performance could be the lack of this support.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation